STRATEGI PENGEMBANGAN USAHA NELAYAN PANCING ULUR DI DOK 9 TANJUNG RIA KOTA JAYAPURA - Tuhumena, Lolita Constantia; Sinaga, Yohana Yana; Rumahorbo, Basa Tunggul; Warpur, Maklon; Tomasila, Leopold Arthur; Pattinaj, Yvonne Indrajati (Universitas Pattimura, 2026)
Fishing boat operators at Dock 9 Tanjung Ria, Jayapura City, face various internal and external constraints that affect their productivity and welfare, such as limited capital, low technical knowledge, weather conditions, and fluctuations in the fishing season. This study aims to analyze the social, economic, and technical conditions of fishing boat operators and formulate strategies for developing their businesses. This study uses a survey method with primary data collection through interviews, questionnaires, and observations, as well as secondary data from relevant agencies from August 2025 to January 2026. The research population consisted of 30 longline fishermen who catch yellowfin tuna (Thunnus albacares), as well as descriptive data analysis and SWOT analysis. The results show that longline fishermen are predominantly aged 30 to 39 years old, with a primary school education, 6 to 10 years of business experience, and ≤3 dependents, and they don’t pay any levies to the government. Meanwhile, the recommended development strategies include optimizing the sustainable use of fishing gear, improving facilities and infrastructure, strengthening marketing cooperation, diversifying processed products, and increasing access to capital to improve the welfare of fishermen in Dock 9, Jayapura City, Papua Province.